Analisis Faktor yang Berhubungan dengan Janin Letak Sungsang - Esti Dwi Yulianita; Rafhani Rosyidah (Malahayati Nursing Journal, 2025)
ABSTRACT Breech presentation is one of the leading causes of maternal mortality, although it occurs in only 2-3% of pregnancies, it carries significant risks of complications, including an increased risk of maternal death by 20-30%. The purpose of this study is to analyze the factors associated with breech presentation. This study uses an analytical design with a Cross-Sectional approach to analyze the relationship between several factors such as age, parity, polyhydramnios, maternal height, and placenta previa with the incidence of breech presentation. The study population consists of third-trimester pregnant women with a gestational age of 36-42 weeks who meet the inclusion criteria. The sample size of this study is 114 pregnant women in each group, calculated using the Lemeshow formula. Data was collected secondarily from medical records and analyzed using univariate analysis through frequency distribution tables, bivariate analysis using the chi-square test with a significance level of 0.05, and the prevalence of breech delivery was calculated using Prevalence Ratio (PR).  Keywords: Breech Presentation, Pregnancy, Risk Factors.  ABSTRAK Sungsang menjadi salah satu penyebab utama angka kematian ibu, yang walaupun hanya terjadi pada 2-3% kehamilan, tetapi memiliki risiko komplikasi yang signifikan, termasuk peningkatan risiko kematian ibu hingga 20-30%. Tujuan penelitian ini adalah menganalisis faktor yang berhubungan dengan janin letak sungsang. Penelitian ini menggunakan desain analitik dengan pendekatan Cross Sectional untuk menganalisis hubungan antara beberapa faktor seperti usia, paritas, hidramnion, tinggi badan ibu, dan placenta previa dengan kejadian letak sungsang. Populasi penelitian adalah ibu hamil trimester III dengan usia kehamilan 36-42 minggu yang memenuhi kriteria inklusi. Biesar sampiel pienielitian ini adalah 114 ibu hamil tiap kielompok yang di hitung mienggunakan rumus Liemieshow. Data dikumpulkan secara sekunder dari rekam medis dan dianalisis menggunakan analisis univariat dengan menggunakan tabel distribusi frekuensi, analisis bivariat dengan menggunakan uji chi – square dengan tingkat kemaknaan 0,05 serta besar prevalensi persalinan sungsang dihitung menggunakan RP (Rasio Prevalensi). Kata Kunci: Letak Sungsang, Kehamilan, Faktor Resiko.